한국 폐경 후 여성의 비타민 D 섭취와 우울증 - 2022년 국민건강영양조사 자료를 이용하여 - 김진아(Jin-A Kim); 이심열(Sim-Yeol Lee) (동아시아식생활학회지, 2024)
This study examined the relationship between vitamin D intake and depression in Korean postmenopausal women. The subjects included 1,224 Korean postmenopausal women who participated in the National Health and Nutrition Examination Survey in 2022. The subjects were divided into quartiles based on their dietary vitamin D intake. Compared to the highest quartile, those in the lowest quartile of vitamin D intake tended to have lower education levels, lower household incomes, and poorer health habits, such as less walking, higher rates of abdominal obesity, elevated blood pressure, and lower HDL cholesterol levels. Depression prevalence was lower in the highest quartile of vitamin D intake (p<0.05). Higher vitamin D intake correlated with a lower odds ratio for depression (p for trend <0.01). These findings suggest that vitamin D intake is significantly related to depression. The promotion of a diet rich in vitamin D may help prevent depression in postmenopausal women. KCI Citation Count: 0